Reproductive biology of a tropical catfish, Mystics nemurus Cuvier & Valenciennes, in Chenderoh reservoir, Malaysia - Khan, M.S.; AMBAK, M.A.; Ang, K.J.; Mohsin, A.K.M. (Wiley Blackwell, 1990)
Abstract. The reproductive biology of a popular and abundant freshwater catfish, Mystus nemurus Cuvier & Valenciennes, was examined, including sex ratio, gonadosomatic index, ova diameter and fecundity. The numerical ratio of male to female was 1:1.06 and was not significantly different (P > 0.05). Mean female gonadosomatic indices (GSI) in April and September corresponding to north‐east and south‐west monsoons were significantly different (P < 0.05) from the dry season (May, June, July and August). Thus the apparent GSI maxima in April and September were indicative of peak spawning period. However, there were no significant differences (P > 0.05) in the fluctuation of the measure of GSI except for those in the dry months, which probably suggested the existence of a protracted breeding season. Mean male GSI in February and November were similarly significant (P < 0.05) to the dry season, although not statistically different (P > 0.05) from those of January, March, April, July, August, October and November. This was probably attributable to an extended breeding period with spawning peaks in February and November corresponding to early and late monsoons. The aseasonal reproduction is common in tropical fishes. GSI were positively correlated with rainfall and water level fluctuations. Fecundity varied from a minimum 6900 to a maximum 93510 in specimens with total lengths of 34.8cm and 45.0cm respectively. Fecundity was found to increase linearly with length and weight and was significantly different (P < 0.05) from them.